Konsep Kepemimpinan dalam Persfektif Islam - Ahmad Al Gufron; Cecep Anwar (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Leadership is the process of influencing others to achieve a common goal. In the Islamic perspective, leadership is very important something that is beneficial for the welfare of mankind, both on a small and large scale. Not only achieving the goals of an organization, institution, company, or state, leadership in Islam is a testament to faith and devotion to Allah swt. Therefore, we need a leader who has a characteristic leadership spirit that is in accordance with Islamic teachings. This study aims to find out what are the characteristics of leadership in Islam? perspective. This research is a type of library research. Documentation is a data collection technique used in this study. Data analysis was carried out using qualitative descriptive data analysis techniques. The results of this study indicate that the characteristics of leadership in an Islamic perspective include (aa) being Muslim, having faith and piety to Allah swt, (b) consistent aqidah strength, (c) solely because of Allah swt., (d) love of truth. , (e) male, (f) has four characteristics of the apostle (tabligh, siddiq, amanah, fathonah), (g) does not ask for office, (h) is fair, (i) does not accept gifts, (j) patient, does not arrogant, gentle and humble, (k) hard work, firm, disciplined, consistent and consistent, (l) selflessness, (m) love of people, (n) simple life, (o) willing to sacrifice, and ( p) ) exemplary and pioneers.